24-h ambulatory recording of aortic pulse wave velocity and central systolic augmentation: a feasibility study - Luzardo, Leonella; Lujambio, Inés; Sottolano, Mariana; da Rosa, Alicia; Thijs, Lutgarde; Noboa, Oscar; Staessen, Jan A; Boggia, José (Hypertension research, 2012)
We assessed the feasibility of ambulatory pulse wave analysis by comparing this approach with an established tonometric technique. We investigated 35 volunteers (45.6 years; 51.0% women) exclusively at rest (R study) and 83 volunteers (49.9 years; 61.4% women) at rest and during daytime (1000-2000 h) ambulatory monitoring (R+A study). We recorded central systolic (cSP), diastolic (cDP) and pulse (cPP) pressures, augmentation index (cAI) and pulse wave velocity (PWV) by brachial oscillometry (Mobil-O-Graph 24h PWA Monitor) and radial tonometry (SphygmoCor). We applied the Bland and Altman's statistics. In the R study, tonometric and oscillometric estimates of cSP (105.6 vs. 106.9 mm Hg), cDP (74.6 vs. 74.7 mm Hg), cPP (31.0 vs. 32.1 mm Hg), cAI (21.1 vs. 20.6%) and PWV (7.3 vs. 7.0 m s(-1)) were similar (P0.11). In the R+A study, tonometric vs. oscillometric assessment yielded similar values for cSP (115.4 vs. 113.9 mm Hg; P=0.19) and cAI (26.5 vs. 25.3%; P=0.54), but lower cDP (77.8 vs. 81.9 mm Hg; P<0.0001), so that cPP was higher (37.6 vs. 32.1 mm Hg; P<0.0001). PWV (7.9 vs. 7.4 m s(-1)) was higher (P=0.0002) on tonometric assessment. The differences between tonometric and oscillometric estimates increased (P0.004) with cSP (r=0.37), cAI (r=0.39) and PWV (r=0.39), but not (P0.17) with cDP (r=0.15) or cPP (r=0.13). Irrespective of measurement conditions, brachial oscillometry compared with an established tonometric method provided similar estimates for cSP and systolic augmentation, but slightly underestimated PWV. Pending further validation, ambulatory assessment of central hemodynamic variables is feasible.